Rapid preparation of block copolymer templated mesoporous Zr1-xCexO2 thin films - Violi, Ianina Lucila (2017)
A scalable, simple, robust and reproducible method is presented for the preparation of chemically homogeneous and ordered nanocrystalline and mesoporous Zr1-xCexO2 thin films. The method utilizes widely available commercial block copolymers as templates. We show how the preparation conditions, film compositions and thermal treatments determine the mesoporous and crystalline structure. Through the scanning of the synthetic process, it was possible to arrive at an optimized and very reproducible method which allows the preparation of high quality, transparent, nanocrystalline and ordered Zr1-xCexO2 mesoporous thin films with different compositions.